Collagen α1(XI) in normal and malignant breast tissue - Halsted, Karen C (2008)
Little is known about collagen XI expression in normal and malignant breast tissue. Tissue microarrays, constructed from 72 patients with breast carcinoma and matched normal tissue, were immunohistochemically stained with five antisera against isoform-specific regions of collagen α1(XI) N-terminal domain. Staining intensity was graded on a 0–3 scale in epithelial cytoplasm, stroma, and endothelial staining of the vasculature of each tissue core. The staining was compared to known pathologic parameters: age, tumor size, overall tumor grade, nuclear grade, tubule formation, mitotic counts, angiolymphatic invasion, node status, estrogen receptor status, progesterone receptor status, and HER-2/neu status. Estrogen and progesterone receptor status were used as a control for comparison. With antisera V1a and amino propeptide (Npp), stroma surrounding cancerous cells was found to have decreased collagen α1(XI) staining compared to stroma adjacent to normal epithelium (P=0.0006, P<0.0001). Collagen α1(XI) staining with V1a antiserum in cytoplasm of cancer cells demonstrated decreased intensity in metastasized primary tumors when compared to nonmetastasized primary tumors (P=0.009). Cytoplasmic staining with Npp antiserum in cancer demonstrated an inverse relationship to positive estrogen receptor status in cancer (P=0.012) and to progesterone receptor status (P=0.044). Stromal staining for Npp in cancerous tissue demonstrated an inverse relationship with tubule formation score (P=0.015). This is the first study to localize collagen XI within normal and malignant breast tissue. Collagen α1(XI) appears to be downregulated in stroma surrounding breast cancer. Detection of collagen XI in breast tissue may help predict women who have lymph node metastases.